Progress of Selected Products upto 30th September, 1957 - (:unkn) unknown (Planning Commission, 1957)
The Progress Report on Selected Projects (Up to September 30, 1957) provides a detailed overview of India’s industrial and infrastructural initiatives during the early stages of the Second Five-Year Plan. The report covers major steel plants (Bhilai, Durgapur, Rourkela), fertilizer projects (Sindri, Nangal, Rourkela), hydroelectric and irrigation schemes (Bhakra-Nangal, Damodar Valley, Koyna, Rihand, Mahanadi Delta), and power generation projects, alongside telecommunications and electrification efforts. Significant progress is noted, with many projects nearing completion in land acquisition, civil works, and equipment installation, while others remain in design or tender stages. Employment impact is substantial, with thousands of skilled and unskilled workers engaged across sites. Challenges include weather-related delays, administrative hurdles, and tender/funding bottlenecks. The report underscores the cumulative role of these projects in enhancing industrial output, expanding irrigation and power infrastructure, and fostering economic growth, while recommending continued monitoring to achieve planned timelines and outputs.
Statistics and Surveys Division
Statistics and Surveys Division
Keywords: Industrial Projects; Infrastructure Development; Steel Plants; Fertilizer Projects; Hydroelectric Projects; Irrigation Schemes; Power Generation; Employment Impact; Project Delays; Financial Outlay; Tube Wells; Economic Growth